Discomforts, opposition and resistance in schools: the perspectives of union representatives. Issue 7 (3rd October 2018) - Maguire, Meg; Braun, Annette; Ball, Stephen
Abstract: This article draws on case studies of four English schools to explore some of the ways in which trade union representatives in these schools see their roles and the role of their unions in relation to how policy gets done in their schools. The article attempts two things. First, it details and describes some discomforts, oppositions and resistances that are evident in these schools in relation to some of the educational reforms and policy imperatives that are in play. Second, the article connects these empirical instances to an understanding of resistance that embraces subtlety, contingency and contradiction, as well as the elision of accommodations and resistances that can occur, in order to trouble what is sometimes taken as 'a high level of compliance amongst teachers' in neoliberal times.